Cycle route network development and evaluation using spatial multi-criteria analysis and shortest path analysis - Vorster, James Michael (Department of Civil Engineering, 2019)
The current global trend of urbanisation has resulted in many cities today with growing transportation problems. Locally, South Africa is dealing with both urbanisation and spatial inequalities as a result of the apartheid era, with the poor very often located on the outskirts of urban areas, and therefore far from centres of employment and other amenities. Active mobility in the form of walking and cycling have been suggested as a means to address urban transport challenges, as it simultaneously promotes sustainability and improves the liveability of cities. Moreover, the infrastructural requirements for active mobility are far less when compared to motorised transportation, freeing up more land and funding for the development of community amenities. Cycling is an efficient way of travelling in urban areas over short to medium distances for a variety of trip purposes, including commuting to work or school, as a feeder to public transport services, to shops, for leisure trips, or tourism. The planning of cycle routes networks is, however, challenging as traditional methods are incapable of adequately dealing with the conflicting objectives of stakeholders and multiple spatial criteria used to measure these. Moreover, the route qualities desired by cyclists are rarely included in the design of routes. Instead a pre- or post-evaluation of route alternatives against the aforementioned route qualities is performed, which once again is not adequately addressed in the current methods given the conflicting objectives and multiple criteria noted earlier. Traditional processes are also criticised for not being open and transparent, leaving many stakeholders dissatisfied. To address these concerns, the proposed method takes advantage of the powerful set of tools for the manipulation and analysis of spatial information provided by Geographical Information Systems (GIS), and the techniques available in Multi-Criteria Analysis (MCA) for structuring decision problems, and designing, evaluating and prioritising alternatives. This combination, known as Spatial Multi-Criteria Analysis (SMCA), can be thought of as a process that transforms and combines geographical data and the value judgements of stakeholders to obtain information for decision making. The advantages gained from combining GIS and MCA results in the development of an effective Spatial Decision Support System (SDSS). In addition to developing and evaluating a network of cycle routes, the proposed method provides an additional means of prioritising infrastructural requirements using a metric known as Cycle Route Directness (CRD). This compares the network route distance to the Euclidean distance and where the threshold value is exceeded, it can be argued that additional cycle infrastructure is required to reduce the detour by bringing the CRD to below the threshold value. The study uses SMCA to develop a network of optimal routes, which focuses around the needs of cyclists while taking account of other stakeholder requirements, for a defined area in the metropolitan of Port Elizabeth in South Africa. The relatively flat terrain, temperate climate and proximity of poorer income areas to more affluent areas and places of employment made this an ideal area to act as a proof of concept for the proposed method. The case study showcases the method’s ability to act as a SDSS for cycle route network planning at a strategic level.